Physiological and sanitary quality of soybean seeds in response to harvest delay - Conceição Sousa, Carlos Henrique (2024)
Delays in soybean harvesting can limit seed viability and vigor. In this study, soybean cultivar seeds’physiological and sanitary quality was evaluated in response to harvest delay. The experimental design used was completelyrandomized blocks, arranged in a split-plot scheme, with three replicates. The plots were represented by the cultivation of twosoybean cultivars (BMX Bônus IPRO and BMX Olimpo IPRO), while the subplots were represented by three harvest times [0, 7, 14 days afterthe seed’s full maturity (stage R8)]. The following characteristics of the physiological and sanitary quality of the seeds weremeasured: water content, plant emergence, total dry matter, germination, accelerated aging, electrical conductivity, and seedhealth. The delay in the soybean harvest affects the seeds’ physiological and sanitary quality. Seeds harvested seven days afterfull maturity have a higher incidence of Aspergillus flavus and Macrophomina sp. In comparison, seeds harvested 14 days afterfull maturity have a higher incidence of Phomopsis sp. and Fusarium sp.